Pollutant source or sink? Adsorption and mobilization of PFOS and PFOA from sediments in a large shallow lake with extended reed belt. (15th October 2022) - Reif, D.; Zoboli, O.; Wolfram, G.; Amann, A.; Saracevic, E.; Riedler, P.; Hainz, R.; Hintermaier, S.; Krampe, J.; Zessner, M.
Abstract: In this study, we i) assessed the occurrence of perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) in sediments, pore water, and bulk water from three different areas in Lake Neusiedl, Austria, and ii) investigated mechanisms regulating adsorption and remobilization of these substances under different conditions via multiple lab-scale experiments. The adsorption capacity was mainly influenced by sediments' organic matter content, oxide composition, and pre-loading. Results suggest that a further increase of PFAS-concentrations in the open lake can be partly buffered by sediment transport to the littoral zone and adsorption to sediments in the extended reed belt. But, under current conditions, the conducted experiments revealed a real risk for mobilization of PFOS and PFOA from reed belt sediments that may lead to their transport back into the lake. The amount of desorbed PFAS is primarily dependent on water/sediment- or pore water/water-ratios and the concentration gradient. In contrast, water matrix characteristics and oxygen levels played a minor role in partitioning. The highest risk for remobilizing PFOS and PFOA was observed in experiments with sediments taken near the only major tributary to the lake (river Wulka), which had the highest pre-loading. The following management advice for water transport between high and low polluted areas can be derived based on the results. First, to reduce emissions into Lake waters from polluted tributaries like the Wulka river, we recommend diffuse pathways through the reed belt in the lake's littoral to reduce pollutant transport into the Lake and avoid high local sediment loadings. Second, water exchange with dried-up areas with probable higher loadings should be carefully handled and monitored to avoid critical back transport in the open lake. And third, general work in the reed belt or generally in the reed should be accompanied by monitoring to prevent uncontrolled remobilization in the future. Highlights: First study on PFAS transport between higher and less polluted lake compartments. Sediments from the reed belt of a shallow lake offer remaining adsorption potential. Sediment-water ratio and concentration gradient are primary drivers for desorption. A reduction of the sediment's PFAS loadings reduces the risk of remobilization. Further efforts to identify areas with a high risk for PFAS remobilization are needed.